72.2k views
4 votes
What is (f·g)(x)?

f(x)=x^2+2x−6

g(x)=x^4+3

User Lalit Rane
by
5.6k points

1 Answer

7 votes


f(x)=x^2+2x-6\\\\g(x)=x^4+3


(f\cdot g)(x)=f(x)\cdot g(x)

Use FOIL (a + b)(c + d) = ac + ad + bc + bd


(f\cdot g)(x)=(x^2+2x-6)(x^4+3)\\\\=(x^2)(x^4)+(x^2)(3)+(2x)(x^4)+(2x)(3)+(-6)(x^4)+(-6)(3)

Use
a^n\cdot a^m=a^(n+m)


=x^(2+4)+3x^2+2x^(1+4)+6x-6x^4-18\\\\=x^6+3x^2+2x^5+6x-6x^4-18\\\\\boxed{(f\cdot g)(x)=x^6+2x^5-6x^4+3x^2+6x-18}

User Andriy Zakharko
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.